2014
DOI: 10.1016/j.media.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Organ-focused mutual information for nonrigid multimodal registration of liver CT and Gd–EOB–DTPA-enhanced MRI

Abstract: Accurate detection of liver lesions is of great importance in hepatic surgery planning. Recent studies have shown that the detection rate of liver lesions is significantly higher in gadoxetic acid-enhanced magnetic resonance imaging (Gd-EOB-DTPA-enhanced MRI) than in contrast-enhanced portal-phase computed tomography (CT); however, the latter remains essential because of its high specificity, good performance in estimating liver volumes and better vessel visibility. To characterize liver lesions using both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Conversely, Fernandez-de-Manuel et al [36] proposed a liver-focused deformable registration algorithm using high SNR gadoxetate disodium-enhanced 3D T1-weighted HBP images for liver lesion evaluation. In their study, they reported a mean intra-observation distance of 7.07 mm after registration, which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Fernandez-de-Manuel et al [36] proposed a liver-focused deformable registration algorithm using high SNR gadoxetate disodium-enhanced 3D T1-weighted HBP images for liver lesion evaluation. In their study, they reported a mean intra-observation distance of 7.07 mm after registration, which is similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Select past studies that looked at the CT‐MRI liver region registration according to the MIDRAS (Results of a M ulti‐ I nstituion D eformable R egistration A ccuracy S tudy) have found that the average error ranged from 3.9 to 6.5 mm for different registration approaches . More recently, the study by Manuel et al 2014 used an organ‐focused mutual information approach for the purpose of registering CT and Gd‐EOB‐DTPA MRI has reported a median landmark‐based error of 6.86 mm, and a median surface‐based mean error of 3.23 mm . Furthermore, the majority of selected studies tended to acquire images on the same day, or in the case of Manuel et al 2014 , the MRI scans did not correspond to patients who had undergone radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Landmarks indeed represent another common way to evaluate DIR accuracy. 75 In order to avoid the invasiveness of implanted surrogates, 71 corresponding anatomical landmarks are usually extracted manually 15,27,34,[76][77][78][79][80][81][82] and then used to compute their distance (or the so-called Target Registration Error, if landmarks are within the tumor). 51 Landmark techniques are, however, limited with poor image quality and contrast.…”
Section: A Operator-dependent Strategies: Image-basedmentioning
confidence: 99%